Modelagem matemática: possibilidade de reflexão sobre temáticas ambientais no ensino médio - NEVES, Renata Rayeth Cabral das (2022)
His research aimed to analyze aspects that show if the use of Mathematical Modeling encourages the reflection of high school students on environmental issues. A research was developed in a qualitative approach with high school students from a public school in Castanhal/PA. One research involved the completion of a questionnaire applied to teachers, as well as two activities with the theme of deforestation in the Castanhal microregion. As environmental issues provided for an application-rich environment, they enable the integration of student experiences with Math and enable the collection of data and information, forms, and problem-solving. How generated discussions contributed for students to understand the need for conservation of natural resources, viewing Mathematics as an instrument of analysis and interpretation of reality. The data from this research reveal that Mathematical Modeling embedded in environmental problems provides a more meaningful school environment, or fact that made students become more critical and reflect on the problems of their reality.